Financial Management in Digital Enterprise Start-up Business (Edutech Company Case Study Tangguh Family) - Linda Gusfita Santosa Putri; Hadi Sumarsono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The times have had an impact on the emergence of Start-up companies in the world, including Indonesia. Start-ups are companies that are just at the development or research stage to find markets and develop products. The scope of start-ups is engaged in e-commerce or online trading of both products and services, which are usually start-ups are also called digital-based companies. One of them is the Tangguh Family edutech start-up. Tangguh Family is a technology company that focuses on education and consulting-based services. The services provided include pre-marital training, marriage content education, family and parenting development, consultation, and discussion forums related to marriage. This research was conducted to project financial reports for 36 months or 3 years at the Tangguh Family edutech Start-up because this Start-up is still new, so good financial reports are needed so that investors are interested in investing. This projection will make it easier for the company to see what will happen in the next few years. This research is a type of applied research using forecasting methods in implementing the Tangguh Family Start-up project. The results of this study are that in the process of developing the Tangguh Family digital start-up, there are important things to attract investors to invest, namely the company's financial statements can be seen from the profit/loss report and cash flow.